Strengthening Inter-Agency Collaboration Through an Integrated Implementation Model in the Social Rehabilitation Program for People with Physical Disabilities at UPT Bina Daksa Pasuruan - Vincentius Andhi Purnama; Sedarmayanti Sedarmayanti; Priyanto Priyanto; Md. Safaet Hossain (International Journal of Social Science and Humanity, 2025)
This research examines the strengthening of inter-agency collaboration through an integrated implementation model in the social rehabilitation program for people with physical disabilities at UPT Bina Daksa Pasuruan, East Java, Indonesia. The social rehabilitation program for persons with disabilities faces significant challenges in coordination, resource allocation, and service integration among multiple stakeholders, including government agencies, non-governmental organisations, and community groups. This study employs a qualitative case study design, using in-depth interviews, focus group discussions, and document analysis to collect data from program implementers, beneficiaries, and related stakeholders. The findings reveal that effective inter-agency collaboration requires five key elements: shared vision and goals, clear communication channels, adequate mechanisms for resource sharing, strong leadership commitment, and continuous monitoring and evaluation systems. The integrated implementation model developed in this study emphasises horizontal and vertical coordination, participatory planning, capacity building initiatives, and community empowerment strategies. The results demonstrate that strengthening inter-agency collaboration through this integrated model significantly improves program effectiveness, service quality, and beneficiary satisfaction. This research contributes to the theoretical understanding of collaborative governance in disability services and provides practical recommendations for policymakers and practitioners in developing countries